Entrepreneurial Affect and Emotions in Entrepreneurship Education Impact Research: A Systematic Review and Research Agenda. (October 2019) - Keller, Pierre G.; Kozlinska, Inna
In this research article, we systematically review literature on entrepreneurial affect and emotions in entrepreneurship education (EE) impact studies. In view of the increasing usage of entrepreneurial affect in the EE literature and the multiplicity of its facets, the main aim of this article is to create a definitional framework of affect. Based on the criteria of scientific standard and relevance for EE, we critically select 46 literature sources published from 1984 to 2017 and conduct a citation analysis of their impact. We then systemize and classify these sources using co-citation analyses as well as conduct a critical review of content similarities. As a result, we identify five main groups of the literature sources: (a) Affect in entrepreneurship research, (b) Affect in EE impact research, (c) Affect-cognition relationship, (d) Affect-conation relationship, and (e) Conceptual contributions. Our critical review of the literature sources further leads to the creation of the definitional framework of affect. The framework facilitates deeper understanding of affect and advocates terminological precision. It may, therefore, serve other EE researchers in conducting impact studies. In this vein, we formulate propositions for further research by combining the affect infusion model with the theory of planned behavior.